The Effect of Personality Traits on Financial Behavior and the Use of e-Wallet as Intervening Variable - Wicaksono, Seprido; Subiyantoro, Edi; Zuhroh, Diana; Werdiningsih, Sri; Sarasmitha, Citra (Proceedings of International Conference of Graduate School on Sustainability, 2022)
This study aims to examine the effect of personality on financial behavior through the use of an e-wallet. The dependent variable of the study is financial behavior, the independent variable is personality, and the intervening variable is the use of e-wallets. Sampling using convenience sampling method, the respondents used were 78. They were e-wallet users in Malang City and have worked for more than one year in the same job. The data collection technique used a questionnaire with a Likert scale, ranging from 1 = strongly disagree to 5 = strongly agree. Data analysis using Structural Equation Model (SEM). The results showed that personality did not affect the use of e-wallets. While personality affects financial behavior and the use of e-wallets harms financial behavior. Personality has no effect on financial behavior through the use of an e-wallet. Thus, this study concludes that e-wallet users understand the function and use e-wallets as a substitute for cash. In addition, personality does have a direct effect on behavior directly, but if it is indirectly seen through the use of an e-wallet, it does not affect financial behavior. Keywords: personality, e-wallet, financial behavior